2022
DOI: 10.1186/s40538-022-00286-3
|View full text |Cite
|
Sign up to set email alerts
|

The use of osmoregulators and antioxidants to mitigate the adverse impacts of salinity stress in diploid and tetraploid potato genotypes (Solanum spp.)

Abstract: Background Many arid and semi-arid areas endure from extensive salinization of agricultural land. Nevertheless, it must either develop salinity-tolerant varieties or use agronomic treatments to alleviate the symptoms of stress. Although the cultivated potato, Solanum tuberosum L., is relatively salt sensitive, salinity tolerance was demonstrated in several Solanum relatives. Knowledge of genetic variation for salinity tolerance across diverse species is required for breeding of salinity-toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…This study also indicates that GSH treatment has protective roles in lessening the toxic effects of LT on the growth and development of S. lycopersicum . It has been already reported that osmoregulators and antioxidants have a defined role in imparting abiotic stress tolerance like salinity stress 31 Moreover, the absorptive surface area of root (Fig. 8 ) were considerably elevated in GSH-supplied plants than in control and LT plants.…”
Section: Discussionmentioning
confidence: 72%
“…This study also indicates that GSH treatment has protective roles in lessening the toxic effects of LT on the growth and development of S. lycopersicum . It has been already reported that osmoregulators and antioxidants have a defined role in imparting abiotic stress tolerance like salinity stress 31 Moreover, the absorptive surface area of root (Fig. 8 ) were considerably elevated in GSH-supplied plants than in control and LT plants.…”
Section: Discussionmentioning
confidence: 72%
“…Similar results were observed at Solanum tuberosum, Oryza Sativa, Zea mays and Fragaria x ananassa cvs. (Carpıcı et al, 2009;Chunthaburee et al, 2016;Denaxa et al, 2022;Zaki and Radwan, 2022a).…”
Section: Discussion Discussion Discussionmentioning
confidence: 99%
“…In vitro determination of salinity tolerance and morphological changes occurring under salt stresses were studied for different species grown in vitro, as follows: Lycopersicon esculentum (Amini et al, 2007), Crithmum maritimum (Grigoriadou and Maloupa, 2008), Citrus macrophylla (Pérez-Tornero et al, 2009), Solanum sp. (Khenifi et al, 2011;Zaki and Yokoi, 2016;Molnár et al, 2021;Zaki and Radwan, 2022a;Ortega-Albero et al, 2023), Saccharum spp. (Passamani et al, 2017), Stevia rebaudiana (Javed and Gürel, 2019), Spinacia oleracea (Muchate et al, 2019), Triticum turgidum (Ami et al, 2020), Antigonon leptopus (El-Zaiat et al, 2020), Olea europaea (Bashir et al, 2021), Pfaffia glomerata (Fortini et al, 2023), Cicer arietinum (Aasim et al, 2023), Ficus carica (Granata et al, 2023).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…Wang [ 235 ] (2021) used the diploid salt-sensitive material HS66 and salt-tolerant material CE125 to construct salt-tolerant isolates and identified six highly salt-tolerant strains, including P3-403, P3-361, P3-563, P3-441, P3-482 and P3-394. Zaki and Radwan [ 236 ] (2022) examined the salt tolerance of diploid clones and found that PI 275136-6, PI 537025-8 and PI 566738-2 had the highest salt tolerance index in sodium salt screening. For agricultural production, the clones with high salt tolerance can be transplanted to the field and tested for 2n pollen production after flowering.…”
Section: Development and Utilization Of Saline-tolerant Potato Cultivarsmentioning
confidence: 99%